Communication abilities of Croatian and Roma children with mild intellectual disability: Performance on children’s communication checklist (CCC) - Slovenc, Anja; Očurščak Žuliček, Sanja (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Communication and language development in children with (mild) intellectual disability is generally delayed. Roma national minority children are sequential bilinguals, most introduced to the Croatian language upon entering the educational system. Information on communication in the natural context can be obtained through checklists completed by children’s communication partners. Objectives. This study aims to obtain insight into the communication and Croatian language abilities of Croatian and Roma children with mild intellectual disabilities. Method. The study participants were fifty-two children between 9 and 16 years old (22 Croatian and 30 Roma). Their performance on the Children’s Communication Checklist was analyzed and compared to published thresholds and each other. Results. The performance of Croatian and Roma children on the pragmatic composite is comparable to that of British peers with intellectual disability, as both groups scored below the normal range. Only the Roma children performed below clinical thresholds on the Speech and Syntax scale. No group displayed autism features. Mann-Whitney test showed significant differences between the groups in Speech output and Syntax subscales, indicating Roma children’s poorer Croatian language abilities. Overall pragmatic abilities did not differ between the groups. Both groups scored below the threshold on the Coherence and Use of conversational context subscales, showing comparable pragmatic profiles. However, Croatian children outperformed Roma children on the Coherence, Use of conversational context, and Conversational rapport subscales. Conclusion. Roma children use the Croatian language in a way comparable to their Croatian peers despite being less proficient in its structure. Pragmatic abilities should be targeted in children with intellectual disabilities.